Leadership in the Family from the Perspective of Modern Family Jurisprudence - M. Waritsul Firdaus. F; M. Shofwan Taufiq (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
The evolving view in society regarding the status and role of women is still divided into two opposite poles. On the one hand, it is generally argued that women should be in the home, serve their husbands and only have a domestic role. Meanwhile, on the other hand, there is also a growing notion that women should be free in accordance with their right to freedom. In this study, the authors used a type of library research. The primary data source in this study is progressive Muslim fiqh. The secondary data sources are books that support the author to supplement from the primary data source. The result of this study is Q.S. An-Nisa: 34 it is often mistaken that all men are female leaders, including in the family. The word ar-rijal in question is a man in particular, that is, a certain husband because of the consideration of the continuation of the verse because they provide for part of their property. So here is a continuation of the verse God has exaggerated some of them over others, which shows that the man in question is the one who has advantages in various respects from the female